2008
DOI: 10.1007/s12230-008-9032-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Cultivars and Selections from the Colorado Potato Breeding Program

Abstract: Consumers have become increasingly aware of potential health benefits from diets rich in fruits and vegetables. While potato has not yet surfaced as a headline-grabber in this respect, there is increasing evidence that some genotypes may possess health attributes that warrant attention. Plant breeders rely on germplasm biodiversity to advance their programs and are also acutely aware of current marketing trends that relate to health attributes. Investigations of antioxidant properties for over 90 genotypes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
90
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 23 publications
(27 reference statements)
17
90
2
Order By: Relevance
“…These natural antioxidants show potential actions against the risk of several age-related diseases, such as cancer, cardiovascular disease, cataract and macular degeneration (Chuah et al, 2008). Although the phenolic content has been extensively studied for raw potatoes (Rumbaoa, Cornago, & Geronimo, 2009;Stushnoff et al, 2008), there have been many discrepancies regarding the effect of heat treatments on the phenolics and antioxidant activity of potato samples, which could be due to the different processing conditions. Some literature has suggested that a shorter cooking time and lower temperature increased or did not change the total phenolic content and the antioxidant capacity (Blessington et al, 2010;Lachman et al, 2013;Mulinacci et al, 2008;Navarre, Shakya, Holden, & Kumar, 2010;Perla, Holm, & Jayanty, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These natural antioxidants show potential actions against the risk of several age-related diseases, such as cancer, cardiovascular disease, cataract and macular degeneration (Chuah et al, 2008). Although the phenolic content has been extensively studied for raw potatoes (Rumbaoa, Cornago, & Geronimo, 2009;Stushnoff et al, 2008), there have been many discrepancies regarding the effect of heat treatments on the phenolics and antioxidant activity of potato samples, which could be due to the different processing conditions. Some literature has suggested that a shorter cooking time and lower temperature increased or did not change the total phenolic content and the antioxidant capacity (Blessington et al, 2010;Lachman et al, 2013;Mulinacci et al, 2008;Navarre, Shakya, Holden, & Kumar, 2010;Perla, Holm, & Jayanty, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The dietary intake of anthocyanins from colored potatoes has been promoted as a possible means of preventing human cancer and other chronic diseases (Stushnoff et al 2008), as anthocyanins promote antioxidant enzyme activities (Zhao et al 2009). The biosynthetic pathway for anthocyanins and its regulation have been extensively studied as a secondary metabolism pathway in plants (Springob et al 2003;Tanaka et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…But the anthocyanin and polyphenols stability can, however, be affected by several factors such as pH, light, oxygen, enzyme activity, concentration, ascorbic acid and sugars [31,32,33,34]. It should be noted that the content of phenolic / anthocyanin compounds and their stability is also dependent on factors such as genotype, agronomic factors, storage conditions after the harvest, processing and cooking methods [5,35,36,16,26,37]. Although there are many studies demonstrating the effect of these compounds on health, which is responsible in classifying potatoes as a functional food, we need to take in consideration that the levels of polyphenols found in raw and cooked tubers will be different.…”
Section: Evaluation Of Tac and Tpc In Bread Products With Different Pmentioning
confidence: 99%